Epistemologi Kritis: Telaah Pemikiran Hermeneutika Jurgen Habermas - Abd. Kholiq, Moh. Khoirul Fatih (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2021)
Habermas hermeneutic theory is perhaps a new breakthrough to bridge the tension between objectivity and subjectivity, between ideality and reality, between theoretical and practical. And this is an achievement of Habermas in the discipline of hermeneutics. Hermeneutics, which initially focused on the area of ​​idealism, by Habermas has been pulled "forcibly" down to be able to understand the field of empirical realism. Hebermas provides a new breakthrough in understanding text and context, so that the point of view resulting from Jurgen Habermas' critical hermeneutic epistemology is to marry objectivity with subjectivity, between the scientific and the philosophical, between the authentic and the articulate, so that the resulting understanding is more objective and in accordance with the context at hand